2005
DOI: 10.4049/jimmunol.174.4.2258
|View full text |Cite
|
Sign up to set email alerts
|

Multiple β1 Integrins Mediate Enhancement of Human Airway Smooth Muscle Cytokine Secretion by Fibronectin and Type I Collagen

Abstract: Altered airway smooth muscle (ASM) function and enrichment of the extracellular matrix (ECM) with interstitial collagen and fibronectin are major pathological features of airway remodeling in asthma. We have previously shown that these ECM components confer enhanced ASM proliferation in vitro, but their action on its newly characterized secretory function is unknown. Here, we examined the effects of fibronectin and collagen types I, III, and V on IL-1β-dependent secretory responses of human ASM cells, and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…However, TGF-b is an important inducer of ECM protein production by ASM, in particular, fibronectin (36,37). This increased release of fibronectin will in turn promote ASM synthetic function (38,39) and mast cell activation (26,40), as well as transition to fibroblastoid phenotype. This altered phenotype has the capacity to further drive the ASM to a more contractile phenotype, therefore propagating the cycle to promote AHR (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, TGF-b is an important inducer of ECM protein production by ASM, in particular, fibronectin (36,37). This increased release of fibronectin will in turn promote ASM synthetic function (38,39) and mast cell activation (26,40), as well as transition to fibroblastoid phenotype. This altered phenotype has the capacity to further drive the ASM to a more contractile phenotype, therefore propagating the cycle to promote AHR (35).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the matrix ligand contains an RGD sequence which binds to α2β1 integrin to stimulate autologous production of various cytokines. 15) It is well known that fibronectin possess RGD sequence, and facilitates dermal fibroblast migration during wound healing. 16) In this study, fibroblasts cultured on the SILK I showed the enhanced expression of fibronectin, suggesting possible roles of fibronectin in cell migration and scaffold condition for skin fibroblasts wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…IL-1, IL-6 and TNF-α are proinflammatory cytokines expressed by a variety of cell types which encourage host responses typical of early stage wound healing [14,15]. GM-CSF has been shown to play a role in the local activation, recruitment and survival of macrophage lineage cells [15,16]. MCP-1 and RANTES are potent stimulators of monocyte and T-cell migration [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…GM-CSF has been shown to play a role in the local activation, recruitment and survival of macrophage lineage cells [15,16]. MCP-1 and RANTES are potent stimulators of monocyte and T-cell migration [16][17][18]. Overall, this panel of key inflammatory proteins should provide a representation of the β1 subunits' role in inflammatory signaling.…”
Section: Introductionmentioning
confidence: 99%